Measurement of forward Z → e+e− production at √s = 8 TeV - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
A measurement of the cross-section for Z-boson production in the forward region of pp collisions at 8 TeV centre-of-mass energy is presented. The measurement is based on a sample of Z → e+e− decays reconstructed using the LHCb detector, corresponding to an integrated luminosity of 2.0 fb−1. The acceptance is defined by the requirements 2.0 < η < 4.5 and pT > 20 GeV for the pseudorapidities and transverse momenta of the leptons. Their invariant mass is required to lie in the range 60-120 GeV. The cross-section is determined to be σ(pp → Z → e+e−) = 93.81 ± 0.41(stat) ± 1.48(syst) ± 1.14(lumi) pb , where the first uncertainty is statistical and the second reflects all systematic effects apart from that arising from the luminosity, which is given as the third uncertainty. Differential cross-sections are presented as functions of the Z-boson rapidity and of the angular variable φ∗, which is related to the Z-boson transverse momentum.
Im Titel sind "+" und "-" hochgestellt
Im Titel steht "s" unter dem Wurzelzeichen
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, B. Adeva, M. Adinolfi, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, E. Gersabeck, L. Grillo, O. Grünberg, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 664 weitere]
Gesehen am 08.10.2020